CYP3A4 inhibitors may influence the quantification of [123I]I-FP-CIT SPECT scans - Booij, Jan; Yağci, Eda; Sheikh, Zulfiqar H; Chahid, Youssef (European journal of nuclear medicine and molecular imaging, 2024)
Purpose [ 123 I]I-FP-CIT SPECT is an imaging tool to support the diagnosis of parkinsonian syndromes characterized by nigrostriatal dopaminergic degeneration. After intravenous injection, [ 123 I]I-FP-CIT is metabolized for a small part by the enzyme CYP3A4, leading to the formation of [ 123 I]I-nor-β-CIT. [ 123 I]I-nor-β-CIT passes the blood-brain barrier and has a very high affinity for the serotonin transporter (SERT). The SERT is expressed in the striatum and cortical areas. So, at least theoretical, the use of frequently used CYP3A4 inhibitors (like amiodarone) may influence the specific to non-specific striatal [ 123 I]I-FP-CIT ratio. Here we tested this novel hypothesis. Methods Using a retrospective design, we determined the specific to non-specific striatal [ 123 I]I-FP-CIT ratio (using BRASS software) in 6 subjects that were using an CYP3A4 inhibitor and 18 matched controls. Only subjects were included with a normal rated [ 123 I]I-FP-CIT SPECT scan, and all participants were scanned on the same brain-dedicated SPECT system. Results The specific to non-specific (assessed in the occipital cortex) striatal [ 123 I]I-FP-CIT binding ratio was significantly higher in CYP3A4 users than in the control group (3.52 ± 0.33 vs. 2.90 ± 0.78, p < 0.001). Conclusion Our preliminary data suggest that the use of CYP3A4 inhibitors may influence striatal [ 123 I]I-FP-CIT binding ratios. This information, when reproduced in larger studies, may be relevant for studies in which quantification of [ 123 I]I-FP-CIT SPECT imaging is used for diagnostic or research purposes.